2008
DOI: 10.1212/01.wnl.0000319690.82357.44
|View full text |Cite
|
Sign up to set email alerts
|

Gender and ethnic differences in subarachnoid hemorrhage

Abstract: Background and Purpose Mexican Americans (MAs) comprise the largest component of the largest minority group within the United States. The purpose of this study was to examine ethnic and gender differences in the epidemiology, presentation and outcomes after subarachnoid hemorrhage (SAH) in a representative United States community. Targeted public health interventions are dependent on accurate assessments of groups at highest disease risk. Methods All non-traumatic SAH patients older than 44 years were prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
37
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 14 publications
11
37
3
4
Order By: Relevance
“…This finding is consistent with several population-based studies that estimate an increased incidence and mortality in women, but predominantly after the menopause 4,18 . Most previous studies show a higher incidence of SAH after 50 years of age 4,[18][19][20] ; however, in the present study the disparity in mortality rates was detected at a younger age and increased with age. In Colombian women, the mean age of menopause is between 47 and 53 years old 21 ; therefore, this finding suggests that factors involved in the pathogenesis of IA and in inducing SAH begin just before the menopause rather than after, as was previously believed 4,18 .…”
contrasting
confidence: 80%
“…This finding is consistent with several population-based studies that estimate an increased incidence and mortality in women, but predominantly after the menopause 4,18 . Most previous studies show a higher incidence of SAH after 50 years of age 4,[18][19][20] ; however, in the present study the disparity in mortality rates was detected at a younger age and increased with age. In Colombian women, the mean age of menopause is between 47 and 53 years old 21 ; therefore, this finding suggests that factors involved in the pathogenesis of IA and in inducing SAH begin just before the menopause rather than after, as was previously believed 4,18 .…”
contrasting
confidence: 80%
“…44,45 Data reported from non-US populations have shown differing sex-related patterns across countries, with higher SAH incidence among men in Finland and eastern Europe, possibly because of regional differences in risk factor prevalence in men and women. 46 The incidence Table 1.…”
Section: Hemorrhagic Stroke (Sah and Ich)mentioning
confidence: 99%
“…While variability regarding arterial characteristics (e.g., wall thickness, vessel diameter) between populations (sex, ethnicity) has been directly examined in some arterial systems (Eden et al 2008, Lindekleiv et al 2010, Müller et al 1991, Schulz and Rothwell 2001, very little has been reported contrasting the differences in ECA branching pattern between sex and side. This study assessed the origin of the caudal four ECA branches to compare the anatomy of males versus females, and right versus left neck.…”
Section: Introductionmentioning
confidence: 99%